BIO.ECONOMIC OPTIMAL LEVELS OF THE BALI STRAIT SARDINE FISHERY OPERATING IN A FLUCTUATING ENVIRONMENT - Purwanto Purwanto (Indonesian Fisheries Research Journal, 2011)
There was an indication that fishing intensity was not the only factor affecting the abundance of Bali sardine stock.